2008
DOI: 10.1007/s10600-008-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure—aroma correlation of citral oxime esters

Abstract: Citral (3,7-dimethyl-2,6-octadienal, 1) occurs in lemongrass, cubeb, citrus, and other essential oils as a mixture of the E-and Z-isomers in a 7:3 ratio. This aldehyde (1) has a strong lemon odor [1] and is used widely in many perfume compositions.The goal of our work was to develop preparative synthetic methods of citral oxime esters through the reaction of citral oxime (2) with alkylcarboxylic acid anhydrides or alkyl-and arylcarboxylic acid chlorides in the presence of pyridine. The synthesis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Consequently, finding methods dealing with oxime or oxime acetate preparations from natural molecules or starting directly from crude essential oils is of interest and indeed was already reported, albeit involving subsequent purification steps [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, finding methods dealing with oxime or oxime acetate preparations from natural molecules or starting directly from crude essential oils is of interest and indeed was already reported, albeit involving subsequent purification steps [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us demonstrated that natural aldehydes can be extracted in very good yields from essential oils by performing a bisulphite extraction [ 16 ]. As an alternative to the standard oximation procedures realized on the crude essential oils [ 15 ], we propose in the present work to use the carbonyl extract (CE) rich in aldehydes obtained from essential oils by a bisulphite extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Both the monoterpenes and the sesquiterpenes have been extensively studied, and some of them, such as the lactones, have even been proposed for use as natural herbicides (Macías et al 1999). Citral is a mixture of the isomeric acyclic monoterpenes geranial (trans-citral or citral A) and neral (ciscitral or citral B) (Chaimovitsh et al 2010;Djorjdevic et al 2008;Dudai et al 1999) in a 7 : 3 ratio (Dikusar et al 2008).…”
mentioning
confidence: 99%
“…We formerly reported on the synthesis of oxime esters of vanillin and vanillal [1], menthone [2], D,L-, D-(+) and L-(-)-camphor [3], jasmorange [4], citral and veratraldehyde [5,6], cyclo-hexanone [7]. It was established that just the presence of methyl, dimethyl, and isopropyl groups in the molecules of fragrant substances obtained from oximes of menthone , camphor, jasmorange, citral, and veratraldehyde ensured the interaction with the olfactory and taste receptors and led to the feeling of odor or taste [2][3][4][5][6]. The oxime esters of cyclohexanone analogous to oxime esters of menthone [2] did not exhibit promising perfume or taste [7].…”
mentioning
confidence: 99%